How Democracies Die - Levitsky, Steven, Ziblatt, Daniel (Crown, 2018)
how Democracies Die explains the historical establishment of democracy in the United States and what the United States has done to preserve it. It also gives a study into the rise and fall of democracies in other countries. There is the layman description of the fall of democracy through warfare and the undermining of democracy by the rejection of established historical norms.